[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么

来源:学生作业帮助网 编辑:作业帮 时间:2017/08/23 08:36:52
[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么[

[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么
[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么

[﹙a+2b)(a-2b)-(a-2b)²]÷6b=什么
[﹙a+2b)(a-2b)-(a-2b)²]÷6b
=[(a-2b)(a+2b-a+2b)]÷6b
=4b(a-2b)÷6b
=2/3(a-2b)

0
[﹙a+2b)(a-2b)-(a-2b)²]÷6b
= [(a-2b)²-(a-2b)²]
=0÷6b
=0
不知是不是正解呐!

原式=(a²-4b²-a²+4ab-4b²)÷6b
=(4ab-8b²)÷6b
=(2a-4b)/3

[a^2-4*b^2-(a^2+4b^2-4ab)]/6b
=(a^2-4b^2-a^2-4b^2+4ab)/6b
=(2a-4b)/3

(2a-4b)/3

(a²-4b²-a²+4ab-b² )÷6b==(2a-4b)/3